2017
DOI: 10.1093/nar/gkx684
|View full text |Cite
|
Sign up to set email alerts
|

Replication stress-induced endogenous DNA damage drives cellular senescence induced by a sub-lethal oxidative stress

Abstract: Although oxidative stress has been shown to induce senescence and replication stress independently, no study has implicated unresolved replication stress as the driver for cellular senescence in response to oxidative stress. Using cells exposed to increasing concentrations of hydrogen peroxide, we show that sub-lethal amount of exogenous hydrogen peroxide induces two waves of DNA damage. The first wave is rapid and transient while the second wave coincides with the cells transition from the S to the G2/M phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 58 publications
5
57
0
Order By: Relevance
“…Using cells exposed to increasing concentrations of H 2 O 2 , we demonstrated that replication stress-induced endogenous DNA damage was responsible for the establishment of a deep cellular senescent phenotype in response to a sublethal oxidative stress. [89] Taken together, these studies clearly identify oxidants as key effectors of DNA damage leading to the activation of the DDR and cell cycle arrest the induction of cellular senescence. However, these data do not address a possible role for oxidants in the signaling pathways involved in the establishment of the senescent phenotype.…”
Section: Dna Replication Stress-induced Senescence and Oxidantsmentioning
confidence: 82%
See 1 more Smart Citation
“…Using cells exposed to increasing concentrations of H 2 O 2 , we demonstrated that replication stress-induced endogenous DNA damage was responsible for the establishment of a deep cellular senescent phenotype in response to a sublethal oxidative stress. [89] Taken together, these studies clearly identify oxidants as key effectors of DNA damage leading to the activation of the DDR and cell cycle arrest the induction of cellular senescence. However, these data do not address a possible role for oxidants in the signaling pathways involved in the establishment of the senescent phenotype.…”
Section: Dna Replication Stress-induced Senescence and Oxidantsmentioning
confidence: 82%
“…Although, oxidative stress and replication stress had been shown to induce senescence independently, our recently published work was the first report implicating unresolved replication stress as the driver of oxidative‐stress‐induced cellular senescence. Using cells exposed to increasing concentrations of H 2 O 2 , we demonstrated that replication stress‐induced endogenous DNA damage was responsible for the establishment of a deep cellular senescent phenotype in response to a sublethal oxidative stress …”
Section: Oxidants and Cellular Senescencementioning
confidence: 99%
“…17 Oxidative stress can induce DNA damage, which is an important mechanism related to stress-induced cellular senescence. 17 Oxidative stress can induce DNA damage, which is an important mechanism related to stress-induced cellular senescence.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Older age can increase the likelihood of NASH and fibrosis. Older age also increases the risk of death of those with NAFLD (Zhang et al, 2017;Venkatachalam et al, 2017). To study the role of oxidative stress in hepatocyte senescence, we selected an antioxidative agent, huperzine A, to treat an in vitro NAFLD model and tested the status of hepatocyte senescence.…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed that the fatty liver cells had a senescence phenomenon. However, how the hepatocytes become senescent in NAFLD is not very clear.Studies report that oxidative stress plays an important role in cellular senescence and aging (Zhang et al, 2017; Gambino et al, 2013;Venkatachalam et al, 2017). Aging is delayed after inhibiting oxidative stress in mammals (Gambino et al, 2013).…”
mentioning
confidence: 99%